2014
DOI: 10.1111/jvim.12467
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Angiography under Sedation in the Diagnosis of Suspected Canine Pancreatitis: A Pilot Study

Abstract: BackgroundComputed tomography (CT) is highly accurate for diagnosing pancreatitis in humans. The diagnosis of pancreatitis in dogs is based on clinical signs, laboratory findings, and ultrasonographic (US) changes. There are, however, inherent limitations in relying on laboratory and ultrasound findings for the clinical diagnosis of pancreatitis in dogs.Hypothesis/ObjectivesWe hypothesized that CT angiography would be a rapid and reliable method to confirm pancreatitis in dogs compared to ultrasonography. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 33 publications
0
38
0
1
Order By: Relevance
“…Although not routinely utilized in the clinical setting, computed tomographic angiography appears superior to AUS in its ability to visualize overt and subtle pancreatic abnormalities, identify potential complications such as portal vein thrombi, and provide prognostic information. 20 There was no difference in hospitalization period between the PLI pos and the PLI neg group (4 days), which might be explained by the lack of power due to the relatively small numbers of dogs in each group. Studies with larger numbers of dogs would be needed to determine if the duration of hospitalization for dogs with DKA is affected by the PLI result.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although not routinely utilized in the clinical setting, computed tomographic angiography appears superior to AUS in its ability to visualize overt and subtle pancreatic abnormalities, identify potential complications such as portal vein thrombi, and provide prognostic information. 20 There was no difference in hospitalization period between the PLI pos and the PLI neg group (4 days), which might be explained by the lack of power due to the relatively small numbers of dogs in each group. Studies with larger numbers of dogs would be needed to determine if the duration of hospitalization for dogs with DKA is affected by the PLI result.…”
Section: Discussionmentioning
confidence: 86%
“…Currently, there is no consensus regarding optimal noninvasive testing for pancreatitis in dogs and many clinicians rely on both AUS and PLI results. Although not routinely utilized in the clinical setting, computed tomographic angiography appears superior to AUS in its ability to visualize overt and subtle pancreatic abnormalities, identify potential complications such as portal vein thrombi, and provide prognostic information …”
Section: Discussionmentioning
confidence: 99%
“…Thus, CT could allow faster and more complete abdominal evaluation for these patients, but scientific investigation of canine biliary contents in veterinary medicine using CT is minimal . Computed tomography is becoming a more accessible tool and, in some instances, a first choice diagnostic modality for larger dogs . The ability of CT to distinguish between canine gallbladder sludge and mucoceles is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…21 Computed tomography is becoming a more accessible tool and, in some instances, a first choice diagnostic modality for larger dogs. 20,22 The ability of CT to distinguish between canine gallbladder sludge and mucoceles is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This information is important to not only allow more accurate identification of abnormal morphologic changes of the feline pancreas and differentiation of disease, but it may also be useful in developing methodology to assess pancreatic function in cats. Previous canine studies have found multiphase CT valuable in diagnosing pancreatitis and pancreatic neoplasms . In people, CT has been used to evaluate pancreatic endocrine function and predict which patients will become diabetic following pancreatectomy …”
Section: Introductionmentioning
confidence: 99%